Determinação da atividade pozolânica da cinza de bagaço de cana-de-açúcar comparada à sílica amorfa e cristalina - Marcela Maira Nascimento de Souza Soares (2015)
The objective of this study is to determine if it is possible to establish a pozzolanicity scale that correlates the results of different direct and indirect tests using highly reactive additions (silica fume) and less reactive additions (quartz), and to locate the position of sugar cane bagasse ash (SCBA) on the scale. Initially, the materials were selected and characterized, and their density, chemical composition, grain size distribution, specific surface area, structure, and morphology were determined. Multiple testing methods were used to verify pozzolanic activity in pure samples and samples with different levels of substitution of cement by siliceous materials including: difference in electrical conductivity in lime solution, amount of fixed CaO, x ray diffraction, infrared (FTIR), thermal analysis (TGA and DTA) and compressive and flexural strength. Aditional analysis were carried out using scanning electron microscopy-SEM in order to complement the pozzolanicity tests. In order to evaluate the development of calcium silicate hydrate (C-S-H), Ca(OH)2 solution mixed with diverse additions (silica fume, quartz and SCBA) were prepared and the solid products were analysed by x ray and FTIR. The results show that SCBA exhibits pozzolanic activity. It was also observed that the testing methods used display a trend of increasing pozzolanic activity with increasing level of silica fume, except for the mechanical tests. The only tests that result in a linear trend are the electrical conductivity difference and amount of CaO fixed. The SEM images show that the silica fume may aglomerate in cement pastes preventing the expected linear trend of increasing pozzolanic activity with increasing silica fume in some tests. It was found that the SCBA exhibits behavior closer to quartz in a pozzolanicity grading scale in the majority of tests, except for the fixed amount of CaO in which it appears to be closer to the silica fume.